Correction: Alshehri, N.; Guediri, M. Projective Vector Fields on Semi-Riemannian Manifolds. Mathematics 2024, 12, 2914 - Norah Alshehri; Mohammed Guediri (Mathematics)
In our recent paper [1], we stated in Theorem 10 that on an n-dimensional semi-Riemannian manifold <semantics>(N,h)</semantics> with <semantics>n≥2</semantics>, if P is a projective vector field that is also conformal, satisfying <semantics>£Ph=2ψh</semantics>, and the vector field <semantics>ζ</semantics>, dual to <semantics>dψ</semantics>, maintains a consistent causal character, then either P is homothetic or <semantics>ζ</semantics> is light-like [...]